Clay type lithium ore crystal transformation lithium-aluminum synergistic extraction method

By mixing clay-type lithium ore with sodium hydroxide and desilicerator under alkaline conditions and leaching with ion sieve adsorbent, the problem of poor synergistic extraction of lithium-aluminum is solved, and efficient and environmentally friendly lithium is achieved Extraction and separation from aluminum simplifies the process flow and reduces cost and environmental impact.

CN119265429APending Publication Date: 2025-01-07BEIJING MINING & METALLURGICAL TECH GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411460438.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing clay-type lithium ore lithium extraction technology has problems such as high cost, environmental pollution, and difficulty in fully extracting valuable elements, especially the poor effect of synergistic extraction of lithium-aluminum, and the baking process consumes high energy and large equipment losses in traditional processes.

Method used

Under alkaline conditions, clay-type lithium ore is mixed with sodium hydroxide and desilicate agent for solid-liquid separation, lithium is adsorbed by ion sieve for separation, combined with hydrochloric acid washing to extract lithium and aluminum, avoiding the roasting process and achieving one step Coordinated extraction of leaching and valuable elements.

Benefits of technology

The efficient extraction of lithium and the efficient separation of aluminum are achieved. The lithium leaching rate reaches more than 97% and the aluminum leaching rate is more than 90%, reducing aluminum losses, simplifying the process flow, saving energy and environmentally friendly, and improving the comprehensive recycling value of valuable elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265429A_ABST
    Figure CN119265429A_ABST
Patent Text Reader

Abstract

The invention provides a clay type lithium ore crystal form transformation lithium-aluminum synergistic extraction method, and relates to the field of hydrometallurgy. The method comprises the following steps: mixing the clay type lithium ore with sodium hydroxide and a desiliconizing agent, and then leaching to obtain ore pulp; carrying out solid-liquid separation on the ore pulp to obtain sodium calcium hydrogen silicate slag and a lithium-rich aluminum solution; adsorbing lithium in the lithium-aluminum-rich solution by using an ion sieve, and carrying out lithium-aluminum separation to obtain a lithium-loaded ion sieve and an aluminum-rich solution; washing the lithium ion-loaded sieve with hydrochloric acid to obtain a lithium chloride solution; the aluminum-rich solution is used for extracting to obtain an aluminum product. The clay type lithium ore crystal form transformation lithium-aluminum synergistic extraction method provided by the invention has the characteristics of high lithium loading rate, relatively thorough lithium-aluminum separation, environmental friendliness, simple process and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hydrometallurgy, and in particular to a method for the coordinated extraction of lithium and aluminum by converting the crystal form of clay-type lithium ore. Background Art

[0002] Clay-type lithium ore is a new mineral for lithium extraction, which is generally divided into carbonate clay-type lithium ore and volcanic clay-type lithium ore. Its composition includes minerals such as diaspore silicate, and lithium is embedded in the ore. There are three main methods for processing clay-type lithium ore: direct roasting, auxiliary roasting and ion exchange. The more mature method is to first roast the clay-type lithium ore to change the mineral structure, so that lithium is more easily exposed on the surface of the mineral, and then add sulfuric acid for leaching. The temperature required for the direct roasting method is determined by the type of ore, usually 600℃~1200℃. The sulfuric acid roasting method has high energy consumption, the slag is difficult to recover, and valuable metal elements such as aluminum are difficult to recycle, which increases the cost of the roasting method.

[0003] The additive roasting method is to add certain reagents that promote the separation of lithium ions from the original ore during the roasting process into the reaction vessel for roasting to form new lithium compounds, which is beneficial to the subsequent product production. However, compared with the single additive system, the multi-additive system has more additives, which will not only increase the cost of raw materials, but also bring more impurity elements into the leachate, thereby increasing the difficulty of subsequent separation and purification.

[0004] The mechanism of ion exchange is to selectively exchange ions from the solution through coordination and exchange of chemical energy, thereby achieving a metallurgical process without destroying the morphology of the original ore. However, most of the existing experiments use iron salts, and impurity elements are inevitably mixed into the ion exchange process, which increases the difficulty of impurity removal. In addition, the process conditions have not been clearly explored, making it difficult to form a stable clay-type lithium ore extraction system.

[0005] The three existing mainstream methods all aim to strip lithium from the ore, and then leach it after pretreatment with the help of high-temperature roasting, reagent-assisted methods, etc., which has the disadvantages of high cost, environmental pollution, and difficulty in fully extracting valuable elements. The synergistic extraction and enrichment of valuable elements in clay-type lithium ore is not only very important for the efficient utilization of this resource, but also a prerequisite for the full development of new lithium resources. Therefore, in order to reduce costs and improve the comprehensive utilization value of clay-type elements, it is of great significance to develop a process for treating clay-type lithium ore using a crystal transformation method under alkaline conditions.

[0006] In the existing lithium extraction technology for clay-type lithium ore, patent CN116477858A discloses a method for preparing battery-grade lithium carbonate by pressure leaching of clay lithium ore, in which: the clay lithium is first ball-milled and slurried with water, the slurry is pressure-leached with nitric acid, filtered to obtain a leachate and a leached residue, the leachate is subjected to negative pressure evaporation, concentration and crystallization, and the mother liquor and crystals are separated; the crystals are spray-pyrolyzed to obtain industrial-grade aluminum oxide and nitrogen oxides; the mother liquor is membrane-separated to obtain lithium nitrate and aluminum nitrate solutions; the lithium nitrate is evaporated and concentrated under negative pressure to obtain a high-concentration lithium nitrate solution, and then impurities are removed and membrane separation is performed to obtain a nitric acid solution and a lithium hydroxide solution; the lithium hydroxide is evaporated, concentrated and carbonized to obtain battery-grade lithium carbonate. This process extracts and separates lithium and aluminum from the ore simultaneously, but the steps involve nitric acid pressure leaching and membrane separation, which increases the experimental cost and equipment loss. For example, patent CN115725858A discloses a method for extracting lithium from clay-type lithium ore, the steps of which include: crushing the clay-type lithium ore and mixing it with water to form a slurry; letting the mixed liquid stand, taking the upper clear liquid and drying it to prepare the material, and then conveying the ore to an electrostatic field for electrostatic separation to obtain concentrate powder, and performing lithium extraction operations on the concentrate powder to prepare lithium salt. This method is a method for obtaining lithium concentrate by front-end treatment of minerals in clay-type lithium ore, which solves the problem of ore dressing of clay-type lithium ore, but does not solve the problem of lithium-aluminum synergistic extraction; for example, patent CN116002736A discloses a method for separating aluminum and lithium from clay lithium ore to prepare aluminum hydroxide by pressure leaching, and the steps include: S1, ball milling the clay lithium ore; S2, slurrying the clay lithium ore after ball milling in step S1 with water, and then adding nitric acid to the slurry for nitric acid pressure leaching reaction, filtering the solid-liquid mixture obtained by the reaction to obtain leachate and leaching residue; S3, adjusting the pH of the leachate obtained in step S2 in three stages to obtain corresponding filtrate and precipitate; S4, dissolving and filtering the primary precipitate obtained in step S3 with water to obtain crude aluminum hydroxide and lithium nitrate solution; S5, deep impurity removal of the three filtrates obtained in step S3 by resin, and then membrane treatment. The conditions used in this method are nitric acid pressure leaching, and the required equipment requirements are high.

[0007] In summary, most of the methods involved in the existing clay-type lithium ore leaching process are acid leaching, but this process is difficult to comprehensively recover the remaining valuable elements in the clay-type lithium ore. At the same time, the roasting pretreatment of the original ore greatly increases the production cost. In addition, it is necessary to consider the loss and cost of equipment caused by nitric acid in the above-mentioned lithium and aluminum synergistic extraction example. Summary of the invention

[0008] The purpose of this application is to provide a method for the coordinated extraction of lithium and aluminum by converting the crystal form of clay-type lithium ore to solve the above-mentioned problems.

[0009] To achieve the above objectives, this application adopts the following technical solutions: A method for lithium-aluminum synergistic extraction by converting clay-type lithium ore crystal form, comprising: Mixing clay-type lithium ore with sodium hydroxide and a desiliconizing agent, and then leaching to obtain ore pulp; The slurry is subjected to solid-liquid separation to obtain sodium calcium hydrogen silicate slag and lithium-aluminum-rich solution; Adsorbing lithium on the lithium-aluminum-rich solution with an ion sieve to separate lithium from aluminum to obtain a lithium-loaded ion sieve and an aluminum-rich solution; The lithium ion sieve is washed with hydrochloric acid to obtain a lithium chloride solution; the aluminum-rich solution is used to extract an aluminum product.

[0010] Preferably, the mass concentration of the sodium hydroxide is 25-75%.

[0011] Preferably, the liquid-to-solid ratio of the mixture is (2-10) ml:1 g.

[0012] Preferably, the leaching temperature is 180-320° C. and the leaching time is 0.5-5 h.

[0013] Preferably, the desiliconizing agent includes one or more of calcium oxide, calcium hydroxide and lime milk.

[0014] Preferably, the molar ratio of calcium in the desiliconizing agent to silicon in the clay-type lithium ore is (0.5-3):1.

[0015] Preferably, the method satisfies one or more of the following conditions: (1) The ion sieve adsorbs lithium for a time of 0.1-5 hours and an adsorption temperature of 20-80°C; (2) The amount of hydrochloric acid used is 50-300 g of the lithium-ion sieve per liter.

[0016] Preferably, the ion sieve comprises a titanium-based ion sieve.

[0017] Preferably, the preparation method of the titanium-based ion sieve comprises: Lithium hydroxide monohydrate and titanium oxide are ground according to a Li:Ti molar ratio of 2:5-2:10, and then roasted; the roasting preparation includes: heating to 100-500°C at room temperature, keeping the temperature for 1-24 hours, and then heating to 800-1200°C, and keeping the temperature for 1-24 hours; The calcined product is washed with water, the sieve material is sieved, and then soaked with hydrochloric acid, and washed with water until neutral. Preferably, the amount of hydrochloric acid used is 50-300g of the lithium ion sieve per liter.

[0018] Preferably, the clay-type lithium ore contains 0.1wt%-1wt% lithium, 15wt%-30wt% aluminum, and a particle size of -0.150mm, accounting for 80% or more.

[0019] Compared with the prior art, the beneficial effects of this application include: The present invention uses high concentration alkali to dissolve the aluminum element contained in the ore, and cleverly destroys the mineral crystal structure by adding a desiliconizing agent, so that the aluminum and silicon of the diaspore in the original ore can be more easily stripped, and the leaching process is strengthened. The method has the characteristics of high reaction intensity, low vapor pressure, and good filtering performance, and avoids the two-stage process of first roasting and then leaching in the traditional process. By adding a desiliconizing agent, the original slag system diaspore slag is transformed into sodium calcium hydrogen silicate, which is easier to filter and does not contain aluminum in the chemical formula of the slag, ensuring that lithium and aluminum are leached while greatly reducing the loss of aluminum, and the impurities silicon and iron contained in the original ore are retained in the slag, the lithium leaching rate is more than 97%, and the aluminum leaching rate is more than 90%, realizing the coordinated leaching of lithium and aluminum. At the same time, the comprehensive recovery of valuable elements is improved, and it has good economic value.

[0020] The present invention cleverly uses ion sieves to adsorb lithium in strong alkalinity and enrich aluminum at the same time, solving the difficulty of lithium-aluminum separation and ensuring efficient extraction and separation of lithium without destroying the stock solution. The adsorption rate of lithium is above 98%, and the lowest adsorption rate of aluminum is 4.69%.

[0021] The present invention greatly shortens the clay-type lithium ore leaching process through the direct alkaline leaching process, omits the energy-intensive roasting process, achieves one-step leaching and separation and enrichment of valuable elements lithium and aluminum, and has the advantages of simple process, energy saving, environmental protection, and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0023] Figure 1 A schematic diagram of the process flow of the method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal conversion provided in this application; Figure 2 A schematic diagram of the ion sieve adsorption process in the method provided in this application; Figure 3 This is the X-ray diffraction analysis diagram of the titanium-based lithium ion sieve used in the example; Figure 4 This is a scanning electron microscope analysis image of the titanium-based lithium ion sieve used in the example; Figure 5 This is a photo of the titanium-based lithium ion sieve used in the examples; Figure 6 The X-ray analysis diagram of the slag obtained from the first group of experiments in Example 1 and Comparative Example 2; Figure 7 This is a scanning electron microscope analysis diagram of the slag obtained from the first group of experiments in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0024] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows: like Figure 1 As shown, the present application provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal form conversion, comprising: Mixing clay-type lithium ore with sodium hydroxide and a desiliconizing agent, and then leaching to obtain ore pulp; The slurry is subjected to solid-liquid separation to obtain sodium calcium hydrogen silicate slag and lithium-aluminum-rich solution; Adsorbing lithium on the lithium-aluminum-rich solution with an ion sieve to separate lithium from aluminum to obtain a lithium-loaded ion sieve and an aluminum-rich solution; The lithium ion sieve is washed with hydrochloric acid to obtain a lithium chloride solution; the aluminum-rich solution is used to extract an aluminum product.

[0025] The present application provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystals. In the presence of sodium hydroxide, the insoluble diaspore in the ore is fully dissolved to form a raw material sodium aluminate solution in the mainstream method for producing aluminum hydroxide. In the reaction without adding a desiliconizing agent, aluminum, sodium, and silicon will directly generate the product natite Na8Al6Si6O with aluminum. 24 (OH)2(H2O)2 slag, this slag system will carry a large amount of aluminum into the slag and be abandoned, and the aluminum resources cannot be fully utilized, resulting in a waste of resources. Since silicon and aluminum are in the same mineral phase, a large amount of alkali will be consumed in the aluminum-silicon stripping process. In order to keep the aluminum in the leaching solution and silicon in the slag phase, the method of adding a desiliconizing agent is adopted. The nadite will react further to form a sodium calcium hydrogen silicate NaCaHSiO4 slag system. Only silicon enters the slag system and aluminum is retained in the solution, solving the problem of the loss of target aluminum resources in the solution and the separation of silicon impurities. Then the coordinated leaching of the target ion lithium aluminum and the efficient extraction of aluminum are completed.

[0026] In addition, the present application uses a titanium-based ion sieve to adsorb lithium from the lithium-rich aluminum stock solution after solid-liquid separation, and completes the direct separation and enrichment of lithium and aluminum under strong alkaline conditions. The monovalent cationic lithium ions are adsorbed from the solution by ion exchange, and the aluminate anions Al(OH)4 are not adsorbed. - and silicate anion HSiO4 2- , and then complete the separation and enrichment of lithium and aluminum.

[0027] This application can extract lithium and aluminum from clay-type lithium ore in a coordinated manner, and then separate lithium and aluminum through a titanium ion sieve, thereby improving the high-value-added development and utilization of clay-type lithium ore. This method has the characteristics of high lithium loading rate, relatively thorough lithium and aluminum separation, environmental friendliness and simple process.

[0028] In an optional embodiment, the mass concentration of the sodium hydroxide is 25-75%.

[0029] It should be noted that what is referred to here is the mass concentration of the sodium hydroxide aqueous solution.

[0030] The ore mainly contains a large amount of silicon and aluminum elements. If aluminum is to be removed from silicon, the solubility product of the element compound must be combined, and calcium, which is easy to combine tightly with silicon to form a new compound that is more difficult to dissolve, must be introduced to retain the target element aluminum in the solution, achieving the purpose of impurity removal and special leaching, and solving the problem of treating aluminum as gangue in traditional processes, thereby wasting valuable elements.

[0031] Optionally, the mass concentration of the sodium hydroxide can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or any value between 25-75%.

[0032] In an optional embodiment, the liquid-to-solid ratio of the mixture is (2-10) ml:1 g.

[0033] Optionally, the liquid-to-solid ratio of the mixture can be 2 ml:1g, 3 ml:1g, 4 ml:1g, 5 ml:1g, 6 ml:1g, 7 ml:1g, 8 ml:1g, 9 ml:1g, 10 ml:1g or any value between (2-10) ml:1g.

[0034] In an optional embodiment, the leaching temperature is 180-320° C. and the leaching time is 0.5-5 h.

[0035] Optionally, the leaching temperature can be 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃ or any value between 180-320℃, and the time can be 0.5h, 1h, 2h, 3h, 4h, 5h or any value between 0.5-5h.

[0036] In an optional embodiment, the desiliconizing agent includes one or more of calcium oxide, calcium hydroxide, and lime milk.

[0037] In an optional embodiment, the Ca / Si molar ratio of calcium in the desiliconizing agent to silicon in the clay-type lithium ore is (0.5-3):1.

[0038] The calcium-silicon ratio referred to here refers to the molar ratio of calcium in the desiliconizing agent to silicon in the clay-type lithium ore.

[0039] The above proportions and selections ensure that the clay-type lithium ore is fully reacted during the mixing reaction with the added reagents.

[0040] Optionally, the Ca / Si molar ratio of calcium in the desiliconizing agent to silicon in the clay-type lithium ore is 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or any value between (0.5-3):1.

[0041] In an optional embodiment, the method satisfies one or more of the following conditions: (1) The ion sieve adsorbs lithium for a time of 0.1-5 hours and an adsorption temperature of 20-80°C; Optionally, the time for the ion sieve to adsorb lithium can be 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h or any value between 0.1-5h, and the adsorption temperature can be 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or any value between 20-80℃.

[0042] (2) The amount of hydrochloric acid used is 50-300 g of the lithium-ion sieve per liter.

[0043] Optionally, the usage amount of the hydrochloric acid may be 50 g, 100 g, 150 g, 200 g, 250 g, 300 g of the lithium-loaded sieve per liter or any value between 50-300 g of the lithium-loaded sieve per liter.

[0044] In an optional embodiment, the ion sieve includes a titanium-based ion sieve.

[0045] In an optional embodiment, the preparation method of the titanium-based ion sieve comprises: Lithium hydroxide monohydrate and titanium oxide are ground according to a Li:Ti molar ratio of 2:5-2:10 (which can be 2:5, 2:6, 2:7, 2:8, 2:9, 2:10 or any value between 2:5-2:10), and then roasted; the roasting preparation includes: heating at room temperature to 100-500°C (which can be 100°C, 200°C, 300°C, 400°C, 500°C or any value between 100-500°C) ), keep warm for 1-24h (can be 1h, 6h, 12h, 18h, 24h or any value between 1-24h), then heat to 800-1200℃ (can be 800℃, 900℃, 1000℃, 1100℃, 1200℃ or any value between 800-1200℃), keep warm for 1-24h (can be 1h, 6h, 12h, 18h, 24h or any value between 1-24h); The calcined product is washed with water, and the sieved material is sieved; then it is soaked in hydrochloric acid (0.5-5 mol / L), and after soaking, it is washed with water until it is neutral.

[0046] The above-mentioned ion sieve is a titanium-based ion sieve that can selectively adsorb lithium under alkaline or strong alkaline conditions, with a saturated adsorption capacity of 25 mg / g and a specific surface area of ​​4.4314 m 2 / g. There is no need to use high-cost reagents and equipment, which can facilitate mass production of ion sieves. There is no need to add other binders or surfactants. The preparation process is simple and convenient for operators to operate. The above method cleverly uses a two-stage method to roast the ion sieve, which can ensure that the particles will not disintegrate due to sudden high temperatures during the synthesis process, so that the ion sieve can maintain a certain particle size after synthesis. In addition, lithium adsorption experiments were carried out under alkaline conditions, and the adsorption rate of lithium was above 98%, and the cyclic adsorption rate of the lithium ion sieve was above 97%. Through material preparation and a two-stage roasting process, the efficient extraction of lithium by the lithium ion sieve in the alkaline solution is achieved, which has the advantages of simple process, energy saving, environmental protection, and environmental friendliness.

[0047] The essence of this titanium-based ion sieve is that it is not easy to dissolve under alkaline conditions and has characteristic adsorption for lithium. The principle is: the ion sieve carries hydrogen ions after pretreatment, which is H2TiO3. When it comes into contact with the solution, the hydrogen ions will undergo ion exchange reaction with lithium ions that are more easily combined with the ion sieve to form lithium titanate Li2TiO3, thereby adsorbing lithium, while other elements in the solution such as aluminum, a small amount of iron and silicon are not adsorbed, thereby achieving efficient separation of lithium and aluminum in an alkaline system.

[0048] Figure 2 The schematic diagram of the exchange process of ion sieve is shown below. The equation of the exchange process of ion sieve is shown below (A represents the titanate ion TiO3 2- , H represents hydrogen ion, Li represents lithium ion): n +Li + =n +H + ; The desorption mechanism of ion sieve is similar to the adsorption mechanism and is a reverse process. When the lithium-loaded ion sieve needs to be eluted, a hydrochloric acid solution of a certain concentration needs to be prepared. During the elution process, the lithium ions on the ion sieve are exchanged with hydrogen ions again, thereby regenerating the ion sieve, and the eluted solution is a certain concentration of lithium chloride. In this way, the lithium and aluminum in the original solution can be separated and enriched, greatly enhancing the lithium-aluminum synergistic extraction rate.

[0049] By utilizing the characteristic adsorption of lithium by the ion sieve, the lithium in the lithium-rich aluminum solution can be adsorbed in the solution under strong alkaline conditions to form a lithium-loaded ion sieve and an aluminum-rich solution, completing the separation and enrichment of lithium and aluminum, and then washing with a certain concentration of hydrochloric acid to complete the desorption of lithium. This method is a good treatment connection for the solution in the above leaching step, and has the advantages of large separation coefficient, high adsorption rate, and environmentally friendly process.

[0050] In an optional embodiment, the clay-type lithium ore contains 0.1wt%-1wt% lithium, 15wt%-30wt% aluminum, and a particle size of -0.150mm, accounting for 80% or more.

[0051] After fine grinding, the ore powder has a particle size of -0.150mm, accounting for more than 80%, in order to enhance the specific surface area of ​​the ore powder, strengthen the solid-liquid contact opportunities during the leaching process, and thus increase the leaching rate of the target elements.

[0052] The clay-type lithium ore used in the embodiments of the present application originates from Yunnan Province, my country. It is a raw material selected after on-site mining, crushing, and ore blending. According to X-ray diffraction analysis, the main types of materials contained in the ore are roughly: lithium chlorite, diaspore, kaolinite, and a small part is iron oxide ore and anatase.

[0053] The raw material composition is shown in Table 1 below: Table 1 Analysis of main elements of a clay-type lithium ore in Yunnan Province

[0054] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0055] First, the titanium series ion sieve used in the embodiment and its preparation method are introduced as follows: S1, grinding and mixing lithium hydroxide monohydrate and titanium oxide according to a Li:Ti molar ratio of 2:5 for 0.2 h to obtain preliminary particles; S2, the raw materials are mixed evenly and filled into a crucible, which is then placed into a roasting furnace for two-stage roasting. The temperature of the first stage is set at 450°C and kept at this temperature for 15 hours; then it is heated to 900°C again and kept at this temperature for 15 hours, and then sampled after cooling.

[0056] S3, pretreatment of ion sieve. Wash the cooled ion sieve with deionized water, sieve out the fine powder and leave the large particle ion sieve. Add 1mol / L hydrochloric acid solution to the washed ion sieve and soak it for ion exchange, so that Li2TiO3 is converted into H2TiO3 ion sieve precursor. After the acid washing is completed, wash it with deionized water until the pH is neutral, and it can be used as a Li adsorbent in a strong alkaline system.

[0057] Figure 3 This is the X-ray diffraction analysis diagram of the obtained titanium-based lithium ion sieve; Figure 4 This is a scanning electron microscope analysis image of the obtained titanium-based lithium ion sieve; Figure 5 This is a photo of the obtained titanium-based lithium ion sieve.

[0058] S4, conduct an adsorption experiment of the ion sieve. The ion sieve adsorbs lithium, the adsorption time is 3 hours, the adsorption temperature is 50°C, the liquid-solid ratio L / S is 20:1, and a static adsorption experiment is conducted. The sodium hydroxide concentration in the stock solution is 800 g / L, the Li concentration is 0.69 g / L, and the Li adsorption rate is 98.3%.

[0059] S5, performing a desorption experiment of the ion sieve. The lithium-loaded ion sieve has a desorption time of 3 hours, a desorption temperature of 50° C., and a hydrochloric acid concentration of 1 mol / L to obtain an eluted lithium-rich solution.

[0060] S6, repeat step S3 for the desorbed ion sieve to perform a cycle experiment. After three cycles, the cyclic adsorption rate of Li was maintained above 97.5%.

[0061] The adsorption experimental data are shown in Table 2: Table 2 Adsorption test data

[0062] It can be seen from the data results of the examples that the ion sieve has extremely high selective adsorption of lithium in a strong alkaline solution and can better separate the remaining impurity elements in the solution.

[0063] Example 1 This embodiment provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal forms, comprising the following steps: S1, put 30g of clay-type lithium ore (containing Li 0.38%, Al 26.77%, and particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent (Ca / Si=1.05:1) Ca(OH)2 into a reactor container for stirring and leaching, with a liquid-to-solid ratio of 5:1, a reaction temperature of 290°C, and a reaction time of 1h to obtain the first stage slurry; S2, filtering the slurry to obtain lithium-aluminum-rich leaching solution and leaching residue, with a lithium leaching rate of 97.46% and an aluminum leaching rate of 96.47%; S3, using ion sieve to adsorb lithium and separate lithium from aluminum, the adsorption time is 3h, the adsorption temperature is 40℃, and lithium-loaded ion sieve and aluminum-rich solution are obtained, and the lithium adsorption rate is 98.78%; S4, washing the lithium ion-carrying sieve with 200 g / L hydrochloric acid to obtain a lithium chloride solution; S5, aluminum hydroxide is extracted from the aluminum-rich solution by seed separation and the like.

[0064] Example 2 This embodiment provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal forms, comprising the following steps: S1, put 30g of clay-type lithium ore (containing Li 0.38%, Al 26.65%, and particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent Ca(OH)2 (Ca / Si=0.9:1) into a reactor container for stirring and leaching, with a liquid-to-solid ratio of 6:1, a reaction temperature of 260°C, and a reaction time of 1h to obtain the first stage slurry; S2, filtering the slurry to obtain lithium-aluminum-rich leaching solution and leaching residue, with a lithium leaching rate of 97.99% and an aluminum leaching rate of 97.09%; S3, using ion sieve to adsorb lithium and separate lithium from aluminum, the adsorption time is 3h, the adsorption temperature is 40℃, and lithium-loaded ion sieve and aluminum-rich solution are obtained, and the lithium adsorption rate is 98.55%; S4, washing the lithium ion-carrying sieve with 150 g / L hydrochloric acid to obtain a lithium chloride solution; S5, aluminum hydroxide is extracted from the aluminum-rich solution by seed separation and the like.

[0065] Example 3 This embodiment provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal forms, comprising the following steps: S1, put 30g of clay-type lithium ore (containing Li 0.30%, Al 19.96%, and particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent CaO (Ca / Si=1.5:1) into a reactor container for stirring and leaching, with a liquid-to-solid ratio of 6:1, a reaction temperature of 285°C, and a reaction time of 1h to obtain the first stage slurry; S2, filtering the slurry to obtain lithium-aluminum-rich leaching solution and leaching residue, with a lithium leaching rate of 97.37% and an aluminum leaching rate of 95.87%; S3, using ion sieve to adsorb lithium and separate lithium from aluminum, the adsorption time is 5h, the adsorption temperature is 30℃, and lithium-loaded ion sieve and aluminum-rich solution are obtained, and the lithium adsorption rate is 98.61%; S4, washing the lithium ion-carrying sieve with 150 g / L hydrochloric acid to obtain a lithium chloride solution; S5, aluminum hydroxide is extracted from the aluminum-rich solution by seed separation and the like.

[0066] Example 4 This embodiment provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal forms, comprising the following steps: S1, put 30g of clay-type lithium ore (containing Li 0.28%, Al 19.96%, and particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent CaO (Ca / Si=2:1) ​​into a reactor container for stirring and leaching, with a liquid-to-solid ratio of 3:1, a reaction temperature of 265°C, and a reaction time of 1h to obtain the first stage slurry; S2, filtering the slurry to obtain lithium-aluminum-rich leaching solution and leaching residue, with a lithium leaching rate of 98.44% and an aluminum leaching rate of 90.47%; S3, using ion sieve to adsorb lithium and separate lithium from aluminum, the adsorption time is 2h, the adsorption temperature is 20℃, and lithium-loaded ion sieve and aluminum-rich solution are obtained, and the lithium adsorption rate is 97.85%; S4, washing the lithium ion-carrying sieve with 100 g / L hydrochloric acid to obtain a lithium chloride solution; S5, aluminum hydroxide is extracted from the aluminum-rich solution by seed separation and the like.

[0067] Example 5 This embodiment provides a method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal forms, comprising the following steps: S1, put 30g of clay-type lithium ore (containing Li 0.36%, Al 25.62%, and particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent Ca(OH)2 (Ca / Si=2.2:1) into a reactor container for stirring and leaching, with a liquid-to-solid ratio of 6:1, a reaction temperature of 270°C, and a reaction time of 1h to obtain the first stage slurry; S2, filtering the slurry to obtain lithium-aluminum-rich leaching solution and leaching residue, with a lithium leaching rate of 97.99% and an aluminum leaching rate of 97.09%; S3, using ion sieve to adsorb lithium and separate lithium from aluminum, the adsorption time is 3h, the adsorption temperature is 40℃, and lithium-loaded ion sieve and aluminum-rich solution are obtained, and the lithium adsorption rate is 98.65%; S4, washing the lithium ion-carrying sieve with 100 g / L hydrochloric acid to obtain a lithium chloride solution; S5, aluminum hydroxide is extracted from the aluminum-rich solution by seed separation and the like.

[0068] In the above embodiments, the leaching rate of silicon is less than 20%.

[0069] Comparative Example 1 Different from Example 1, leaching experiments were conducted at different temperatures (normal temperature) with and without the addition of a desiliconizing agent to observe whether the addition of a desiliconizing agent at normal temperature is helpful for leaching.

[0070] The leaching experiment under normal temperature conditions is as follows: 1. Put 30g of clay-type lithium ore (containing Li 0.36%, Al 25.62%, and a particle size of -0.150mm accounting for more than 80%), 45% sodium hydroxide, and desiliconizing agent CaO (Ca / Si=1.2:1) into a reaction vessel and stir for leaching. The liquid-to-solid ratio is 6:1, the reaction temperature is 100°C, and the reaction time is 3h.

[0071] 2. Put 30g of clay-type lithium ore (containing 0.36% Li, with a particle size of -0.150mm accounting for more than 80%) and 50% sodium hydroxide into a reaction vessel and stir for leaching. The liquid-to-solid ratio is 5:1, the reaction temperature is 100°C, and the reaction time is 3h.

[0072] The reaction results are shown in Table 3 below: Table 3 Comparative Example 1 Results

[0073] From the results, we can see that the first group is a leaching experiment under normal temperature and pressure with the addition of a desiliconizer. Although the reaction time was prolonged, the leaching effect of lithium and aluminum was not good, and silicon was also leached into the solution. The second group is a leaching experiment under normal pressure without the addition of a desiliconizer. Similarly, the leaching rate of lithium and aluminum was not good, and silicon was also leached into the solution, and the effect was not ideal. It can be seen that the crystal transformation temperature of clay-type lithium ore needs to be raised to a certain range to generate sodium calcium hydrogen silicate.

[0074] Comparative Example 2 Different from Example 1, the experiment of crystal transformation was carried out at a temperature of 280°C without adding a desiliconizing agent, and the influence of not adding a desiliconizing agent at 280°C on the leaching results was observed and the situation was analyzed.

[0075] The experiment without adding desiliconizing agent is as follows: 1. Put 30g of clay-type lithium ore (containing Li 0.35%, Al 25.62%, and a particle size of -0.150mm accounting for more than 80%) and 50% sodium hydroxide into a reactor container and stir for leaching. The liquid-to-solid ratio is 6:1, the reaction temperature is 260°C, and the reaction time is 1h.

[0076] 2. Put 30g of clay-type lithium ore (containing 0.35% Li, particle size -100 mesh) and 55% sodium hydroxide into a reactor container and stir for leaching. The liquid-to-solid ratio is 5:1, the reaction temperature is 260°C, and the reaction time is 1h.

[0077] The reaction results are shown in Table 4 below: Table 4 Comparative Example 2 Results

[0078] From the results, it can be seen that under the condition of 280℃, the leaching effect of the two groups without adding desiliconizing agent is not ideal, the aluminum leaching rate is low, and a large amount of silicon enters the solution, making it difficult to separate the target elements lithium and aluminum, and it is impossible to achieve the technical goal of lithium aluminum synergistic extraction. It can be seen that under the condition of not adding desiliconizing agent, the X-ray diffraction detection of the components in the slag system shows that aluminum, silicon and sodium form natite Na8Al6Si6O 24 (OH)2(H2O)2 slag system ( Figure 6 ), compared with the example, the silicon leaching rates of the above two comparative examples are relatively high, and it is difficult to remove the silicon from the solution. After adding the desiliconizing agent, the silicon content in the solution is significantly reduced.

[0079] Taking the added desiliconizing agent Ca(OH)2 as an example, the clay-type lithium ore will undergo the following chemical reaction in the reaction to achieve the purpose of desiliconization of the solution by enriching aluminum. This process involves the galvanite Na8Al6Si6O 24 The chemical reaction equations involved in the formation of (OH)2(H2O)2 and the transformation of nadalite to the sodium calcium hydrogen silicate NaCaHSiO4 crystal form without aluminum inclusions are as follows.

[0080] If no desiliconizing agent is added, the chemical reaction equation is: Li2O+NaOH+aq→LiOH+Na2O+aq; Al2O3·H2O+2NaOH+aq→2NaAl(OH)4+aq; SiO2+2NaOH→Na2SiO3+H2O; Al2O3·H2O·2H2O+6NaOH+aq→2NaAl(OH)4+2Na2SiO3+aq; Na + +HSiO4 2- +Al(OH)4 - →Na8Al6Si6O 24 (OH)2(H2O)2+H2O+10OH - ; If, based on this study, an appropriate amount of desiliconizing agent is added to the system, the chemical reaction equation can be written as: 4NaOH+6Ca(OH)2+Na8Al6Si6O 24 (OH)2(H2O)2+aq→6NaCaHSiO4+6NaAl(OH)4+aq; It should be noted that, from the above chemical reaction equation, it can be seen that in the reaction without adding desiliconizing agent, aluminum, sodium and silicon will directly generate the product natite Na8Al6Si6O with aluminum. 24(OH)2(H2O)2, the slag system will carry a large amount of aluminum into the slag and be abandoned, and the aluminum resources cannot be fully extracted, which directly causes a waste of resources; and the quartz slag system is very difficult to filter and wash. Scanning electron microscopy analysis shows that (such as Figure 7 As shown, a and b are natite slag system, c and d are sodium calcium hydrogen silicate slag system). The natite slag system is spherical particles with irregular surface protrusions. The surface of these mineral particles is extremely easy to adhere to the solution and aggregate and stack, making it difficult to separate the solid and liquid after leaching.

[0081] It should be noted that the experimental principles described above will be confirmed in the embodiments and comparative examples, and the experimental phenomena and experimental results described above are confirmed during the experiment and in X-ray diffraction and scanning electron microscopy analysis.

[0082] It can be seen from the above examples and comparative data that when the clay-type lithium ore is reacted with sodium hydroxide, it is necessary to adjust the ratio of the desiliconizing agent and add it into the reaction container for reaction. By adjusting the calcium-silicon molar ratio of the added desiliconizing agent and the ore, the leaching liquid-solid ratio, and reasonably controlling the leaching temperature and reaction time, the lithium and aluminum valuable elements in the clay-type lithium ore can be efficiently leached together, wherein the lithium leaching rate is more than 98%, and the aluminum leaching rate is more than 90%.

[0083] The present invention cleverly destroys the mineral crystal structure by adding a desiliconizing agent, so that the aluminum and silicon of the diaspore in the original ore can be more easily stripped, and the leaching process is strengthened. The method has the characteristics of high reaction intensity, low steam pressure, good filtering performance, etc., and avoids the two-stage process of first roasting and then leaching in the traditional process. By adding a desiliconizing agent, the original slag system diaspore slag is transformed into sodium calcium hydrogen silicate, which is easier to filter and does not contain aluminum in the chemical formula of the slag, ensuring the leaching of lithium and aluminum while greatly reducing the loss of aluminum, and the impurities silicon and iron contained in the original ore are retained in the slag, realizing the coordinated leaching of lithium and aluminum.

[0084] At the same time, the present invention cleverly uses ion sieves to adsorb lithium in strong alkalinity and enrich aluminum at the same time, solving the difficulty of lithium-aluminum separation and ensuring efficient extraction and separation of lithium without destroying the original solution. The lithium adsorption rate is above 98%.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for the coordinated extraction of lithium and aluminum from clay-type lithium ore crystal transformation, characterized in that: include: Mixing clay-type lithium ore with sodium hydroxide and a desiliconizing agent, and then leaching to obtain ore pulp; The slurry is subjected to solid-liquid separation to obtain sodium calcium hydrogen silicate slag and lithium-aluminum-rich solution; Adsorbing lithium on the lithium-aluminum-rich solution with an ion sieve to separate lithium from aluminum to obtain a lithium-loaded ion sieve and an aluminum-rich solution; washing the lithium ion-carrying sieve with hydrochloric acid to obtain a lithium chloride solution; The aluminum-rich solution is used to extract aluminum products.

2. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: The mass concentration of the sodium hydroxide is 25-75%.

3. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: The liquid-to-solid ratio of the mixture is (2-10) ml:1 g.

4. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: The leaching temperature is 180-320° C. and the leaching time is 0.5-5 h.

5. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: The desiliconizing agent includes one or more of calcium oxide, calcium hydroxide and lime milk.

6. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 5, characterized in that: The molar ratio of calcium in the desiliconizing agent to silicon in the clay-type lithium ore is (0.5-3):

1.

7. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: One or more of the following conditions are met: (1) The ion sieve adsorbs lithium for a time of 0.1-5 hours and an adsorption temperature of 20-80°C; (2) The amount of hydrochloric acid used is 50-300 g of the lithium-ion sieve per liter.

8. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 1, characterized in that: The ion sieve includes a titanium-based ion sieve.

9. The method for lithium-aluminum synergistic extraction from clay-type lithium ore crystal transformation according to claim 8, characterized in that: The preparation method of the titanium-based ion sieve comprises: Lithium hydroxide monohydrate and titanium oxide are ground according to a Li:Ti molar ratio of 2:5-2:10, and then roasted; the roasting preparation includes: heating to 100-500°C at room temperature, keeping the temperature for 1-24 hours, and then heating to 800-1200°C, and keeping the temperature for 1-24 hours; The calcined product is washed with water, and the sieved material is sieved; then, it is soaked in hydrochloric acid, and after the soaking, it is washed with water until it is neutral.

10. The method for lithium-aluminum synergistic extraction by crystal transformation of clay-type lithium ore according to any one of claims 1 to 9, characterized in that: The clay-type lithium ore contains 0.1wt%-1wt% lithium, 15wt%-30wt% aluminum, and a particle size of -0.150mm, accounting for 80% or more.

Citation Information

Cited By

  • Comprehensive utilization method of clay type lithium ore

    CN121204431A